Hubungan Antara Harga Diri Dengan Pengungkapan Diri Pada Remaja Pengguna Media Sosial Instagram - Hasibuan, Ayu Pratiwi; Purba, Anggi Tri Lestari (Jouska: Jurnal Ilmiah Psikologi, 2025)
This study aims to determine the correlation between self-esteem and self-disclosure in adolescent Instagram social media users at MAN Panyabungan.  The research population was students of class X and XI MAN Panyabung and the research sample was 153 students who fit the required characteristics. The sampling technique used was purposive sampling.  This research method uses quantitative methods.  Data collection uses a self-esteem scale and a self-disclosure scale which is measured using a Likert scale.  The data analysis technique used the Product Moment Correlation technique. The results showed that there was a significant positive correlation between self-esteem and self-disclosure in Man Panyabung students.  This result is evidenced by a correlation coefficient of rxy=0.462 with a significance value of p=0.000 0.05.  The self-esteem of Man Panyabung students affects or emphasizes the emergence of self-disclosure in MAN Panyabungam students who use social media Instagram by 21.3%.  From these results it is known that there are still 78.7% of other factors on self-disclosure in MAN Panyabungan students who use Instagram, where these factors are not visible in this study, including self-concept factors, self-awareness, conversation topics, gender.  And MAN Panyabungan students who use Instagram social media have high self-esteem with an empirical average value (empirical mean = 85.18 hypothetical mean = 72.5 where the difference is more than SD number = 6.978) and self-disclosure is high with an average value (empirical mean = 89.54 hypothetical mean = 80 where the difference is more than SD number = 8.215).